BBLR, Pemberian ASI Eksklusif, Pendapatan Keluarga, dan Penyakit Infeksi Berhubungan dengan Kejadian Stunting - Djuhadiah Saadon; Suriani B; Nurjaya Nurjaya; Subriah Subriah (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Stunting is a nutritional problem that hinders the growth process of toddlers. Toddler stunting has a negative impact that will last in the next life. According to UNICEF (2011), the nutritional status of children can be directly affected by factors, namely gender and low birth weight. Indirect factors, namely health status, infectious diseases/ Acute Respiratory Infections (ARI), diarrhea with low family income, parenting patterns, and not exclusive breastfeeding. The aim of the study was to investigate the relationship between low birth weight, exclusive breastfeeding, family income, and infectious diseases with the incidence of stunting in toddlers aged 24-59 months in the Mangasa Health Center Work Area in 2020. This was a case control study involving a total of 30 stunted and non-stunded children in each. The independent variables were low birth weight breastfeeding exclusive, family income, and infectious diseases, while the dependent variable is stunting. The study results show that children with low birth weight were like to have stunting 5.7 times than normal birth weight (p=0.007). Similarly, children with formula and mixed feeding were likely to have stunting 5 times (p=0.015) than exclusively breastfed children. Poor family income and the presence of infectious disease were also contributed to stunting (OR= 7; p= 0.025, OR= 5.7, p= 0.007, respectively). In conclusion, the family income variable is the variable that has the most incidence of stunting among children aged 24 – 59 months.